Thinking too much when facing pressure? The story of decision reinvestment - Laborde, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim of this study was to explore the relationship between decision reinvestment with stress and coping appraisals. From an initial screening of 243 regional handball players, 100 players were selected, and were divided into four groups according to their gender (male vs. female) and to their reinvestment score (high vs. low). Their coping and stress appraisals were assessed during three competitions. Results showed that high reinvesters (HR) players perceive a stress intensity similar to low reinvesters (LR) players, but that they have a lower perception of stressor controllability, coping effectiveness and subjective performance than their LR counterparts. No differences were found in the use of coping strategies between HR and LR players. The tendency to choke under pressure of HR players is discussed according to the saturation of their working memory. Study 1 had two main limitations: 1) the physiological parameters linked with the stress and coping appraisals were not assessed; 2) the subjective performance measure does not reveal the underlying mechanisms explaining the influence of decision reinvestment on performance. Study 2 was designed to address these limitations. Study 2. The aim of this study was to explore the decision-making component of performance through the option-generation paradigm, as well as to assess the physiological reaction to stress based on heart rate variability. Thirty regional handball players (Mage=23.3 years, age range = 17-31 years) took part in this study. In a within-subject design, they were asked to complete an optiongeneration task with 31 3D videos in two conditions, low pressure and high pressure. In addition players were asked to fill in the decisionspecific reinvestment scale, and were attributed after a median split to either the HR or the LR group. Results indicated that the pressure manipulation was successful. In the low pressure condition, no differences in decision-making performance were observed between LR and HR players, Wilks` Lambda=.801 F(6, 23)=.954, p>.05. When comparing the low pressure and high pressure condition, a MANOVA indicated that the overall decision-making performance decreased significantly more in the HR group in comparison to the LR group, Wilks` Lambda=.583, F(6, 23)=2.740, p=.037, eta square=.42. Study 2 showed that decision reinvestment has an influence on the optiongeneration process of the athlete, and that this influence might be associated to a specific physiological activity under pressure. Findings are discussed according to the Thayer`s neurovisceral integration model and to the Take-the-First heuristic.